Apulia. Vol. 1: Neolithic Settlement in the Tavoliere - James, G.D.B (Reports of the Research Committee of the Society of Antiquaries of London, 1987)
One of the by-products of war-time air photography over Italy was the discovery of large numbers of archaeological sites of the prehistoric to medieval periods in the Apulia region of south-east Italy. This volume provides a comprehensive catalogue of the 250 or so Neolithic sites contained within the air-photographic record, a detailed discussion of the environmental background and economic possibilities of the region, and an evaluation of the evidence provided by excavation, notably the Neolithic pottery of the region.